A espiritualidade de Taizé como possibilidade de uma experiência integradora, dialógica e ecumênica do ser humano. - Gastão, Patrícia Gurgel Medeiros (2022)
Postmodernity has implied challenges and profound changes in the integral formation of the human being. Although it is not well defined, in general, it is felt as if the values and ideals that hitherto guided human life, at least in the last few centuries in the West, are now in disrepute. Exacerbated subjectivism, the era of post-truths, relativism and religious pluralism show that the change in the formation of contemporary human beings even reaches their relationship with the transcendent. After all, in a pluralistic and polycentric world, religion is relegated to the private sphere. In the midst of these counterpoints of postmodern dialectics, the present study aims to revisit the spirituality of Taizè as a possibility to recover hope in times of crisis through the primary ideal of communion and brotherhood that integrates the human being. The translational and transductive approach is based on a hermeneutics of texts about human spirituality: A springtime in the Church. Brother Roger and Taizé by Rex Brico; Modernity, pluralism and crisis of meaning by authors Peter Berger and Thomas Luckmann; and in the accounts that collect the religious experience of the brothers of the Taizè Community of Alagoinha/BA. The methodological course is carried out in three moments. At first, it seeks showing positively the possibilities of spiritual development between and beyond the challenges and obstacles arising from postmodernity. In the second moment, it discusses the history of Taizé with emphasis on its spiritual identity in order to highlight its spirituality as a possibility to reintegrate the human being. In the third moment, it seeks to re-propose the spirituality of Taizè as a possibility of an integrative, dialogical and ecumenical experience of the human being. The postmodern crisis refers the needing to rescue spirituality as the ability to reintegrate human beings and reorder relationships with themselves and with the world in which they coexist. The hermeneutic exercise deepens the layers of interpretation, meaning, what spirituality is and how Taizè helps in this search.